Combined effect of tris(2-chloroethyl)phosphate and benzo (a) pyrene on the release of IL-6 and IL-8 from HepG2 cells via the EGFR-ERK1/2 signaling pathway. Issue 85 (27th November 2017) - Zhang, Youjian; Zhang, Wenjuan; Hou, Jian; Wang, Xian; Zheng, Hongyan; Xiong, Wei; Yuan, Jing
Abstract : Tris(2-chloroethyl)phosphate plus benzo (a) pyrene induced inflammatory response in HepG2 cells through the activation of EGFR-ERK1/2 signaling pathway. Abstract : Tris(2-chloroethyl)phosphate (TCEP) and benzo (a) pyrene (BaP) coexist in the environment. Humans are exposed to them via multiple routes every day. Each of them induces hepatotoxicity, which may increase their risk to human health. However, the mechanism underlying the combined toxicity of both compounds in vitro is still unclear. The present study aimed to investigate the molecular mechanism underlying the inflammatory response in the cotreatment of HepG2 cells with TCEP and BaP. The cell viability, and the expression of interleukin (IL)-6 and IL-8 at the mRNA and protein levels were measured in HepG2 cells. The results indicated that TCEP plus BaP decreased HepG2 cell viability, and up-regulated the expression of IL-6 and IL-8 at the mRNA and protein levels. Additionally, the inhibitors of EGFR (AG1478), ERK1/2 (U0126) and p38 MAPK (SB203580) displayed anti-inflammatory properties in the inflammatory response elicited by TCEP plus BaP. The activation of ERK1/2, but not p38 MAPK was inhibited by AG1478. These results indicated that TCEP plus BaP may induce an inflammatory response in HepG2 cells by the activation of the EGFR-ERK1/2 signaling pathway.